2019
DOI: 10.1108/pr-12-2017-0384
|View full text |Cite
|
Sign up to set email alerts
|

Does supervisors’ mindfulness keep employees from engaging in cyberloafing out of compassion at work?

Abstract: Purpose The purpose of this paper is to examine whether the appearance of cyberloafing at work, that is, the use of the company’s internet connection for personal purposes, may be due to a workplace that lacks mindfulness and compassion. The authors first hypothesize that supervisors’ mindfulness is related to the mindfulness of their direct followers, and that both are related to employees’ compassion at work. The authors also hypothesize that compassion mediates the link between supervisors’ and followers’ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 63 publications
0
22
0
1
Order By: Relevance
“…5.3.1.3 Socio-demographic differences. The review suggests that most scholars have utilized socio-demographic indicators, like education (Agarwal and Avey, 2020), marital status (Wu et al, 2020), organizational tenure (Cheng et al, 2020), age and gender (Hensel and Kacprzak, 2020;Zoghbi-Manrique-de-Lara et al, 2019), as control variables. However, few studies have also found socio-demographic-related differences in cyberloafing (Sheikh et al, 2015), the results have been inconsistent.…”
Section: Antecedents and Stakeholdersmentioning
confidence: 99%
“…5.3.1.3 Socio-demographic differences. The review suggests that most scholars have utilized socio-demographic indicators, like education (Agarwal and Avey, 2020), marital status (Wu et al, 2020), organizational tenure (Cheng et al, 2020), age and gender (Hensel and Kacprzak, 2020;Zoghbi-Manrique-de-Lara et al, 2019), as control variables. However, few studies have also found socio-demographic-related differences in cyberloafing (Sheikh et al, 2015), the results have been inconsistent.…”
Section: Antecedents and Stakeholdersmentioning
confidence: 99%
“…For example, gender, Big-Five personality, perceived overqualification, and job demands can all effectively predict employees’ cyberloafing behavior. Similarly, some scholars have examined the impact of leadership styles on cyberloafing, such as abusive supervision ( Agarwal and Avey, 2020 ) and leader mindfulness ( Zoghbi-Manrique-De-Lara et al, 2020 ), but there is still a lack of attention to the multiple leadership styles, particularly the authoritarian leadership prevalent in Chinese organizational context.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that mindfulness significantly reduced mind wandering while using technology such as smartphones. In this line, Zoghbi-Manrique-de-Lara et al ( 2020 ), however, focused their study on exploring leaders’ and followers’ mindfulness. They studied these variables with cyberloafing, compassion and empathic concern.…”
Section: Literature Surveymentioning
confidence: 99%
“…Some research studies regard cyberslacking to be positively associated with employee satisfaction, work motivation and increased communication among employees (Janicke-Bowles, et al, 2019 ; Zoghbi-Manrique-de-Lara et al, 2019 ). Thus, considering cyberslacking as an act of distraction (Lim & Chen, 2012 ), its association with job stress and related phenomenon are areas that are unexplored in literature.…”
Section: Introductionmentioning
confidence: 99%